2015
DOI: 10.1039/c5sm01259g
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche-like fluidization of a non-Brownian particle gel

Abstract: We report on the fluidization dynamics of an attractive gel composed of non-Brownian particles made of fused silica colloids. Extensive rheology coupled to ultrasonic velocimetry allows us to characterize the global stress response together with the local dynamics of the gel during shear startup experiments.In practice, after being rejuvenated by a preshear, the gel is left to age for a time t w before being subjected to a constant shear rate _ g. We investigate in detail the effects of both t w and _ g on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 88 publications
0
37
0
Order By: Relevance
“…It has been seen experimentally in polymeric fluids including wormlike micelles [25,26] and linear polymers [13,[27][28][29]; and in soft glassy materials including carbopol gel [7,30], Laponite clay [31,71], a non-Brownian fused silica suspension [34], and waxy crude oil [69]. Molecular simulations have captured it in polymers [31,72], a model colloidal gel [73], and molecular glasses [32,74,75].…”
Section: A Shear Startupmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been seen experimentally in polymeric fluids including wormlike micelles [25,26] and linear polymers [13,[27][28][29]; and in soft glassy materials including carbopol gel [7,30], Laponite clay [31,71], a non-Brownian fused silica suspension [34], and waxy crude oil [69]. Molecular simulations have captured it in polymers [31,72], a model colloidal gel [73], and molecular glasses [32,74,75].…”
Section: A Shear Startupmentioning
confidence: 99%
“…In startup of steady simple shearing flow (shear startup), for example, the (near ubiquitous) presence of an overshoot in the shear stress startup signal has been identified as a possible trigger for the formation of shear bands, at least transiently, en route to a steady flowing state [7,8,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. A declining time-dependent viscosity has been similarly identified as a trigger for banding following the imposition of a step stress [16][17][18][25][26][27]29,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Although historically described as a mere artifact, wall slip appears as an intrinsic feature of complex fluids that has been reported in polymeric fluids [3][4][5] as well as in soft glassy materials such as colloidal suspensions [6,7], foams [8][9][10], emulsions [11][12][13], microgels [14,15], attractive gels [16], etc. Moreover, wall slip is often non-trivially coupled to the bulk dynamics of complex fluids, especially during the yielding transition where it may even govern the nature of the subsequent steady-state flow [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…turbulent flows. Nevertheless, in all of these studies the velocity fields provided insight in the underlying physics of the observed overall rheological behaviour, hereby "linking global rheology to the local dynamics" (Kurokawa et al 2015). This makes ultrasound-based techniques a very powerful tool in rheology.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…In this case the torque, rather than the pressure drop, is used to quantify viscous losses. Ultrasound speckle velocimetry was used to characterise fatigue due to shear in gels (Gibaud et al 2016), flow banding in cellulose nanofibril suspensions (Martoïa et al 2015), flow instabilities and shear banding in a non-Newtonian micellar solution (Gallot et al 2013) and avalanche-like fluidisation events in suspensions (Kurokawa et al 2015). Again, most of these systems are inherently echogenic and do thus not require seeding.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%